2015
DOI: 10.3923/jm.2015.494.501
|View full text |Cite
|
Sign up to set email alerts
|

First Report of the blaOXA-23 Gene in a Clinical Isolates of Acinetobacter baumannii in Najaf Hospitals-Iraq

Abstract: Carbapenemase producing Acinetobacter baumannii is frequently associated with nosocomial infections. Increasing resistance to carbapenems, may significantly reduce the choice of effective antibiotics. This study was conducted to determine the occurrence of carbapenemase producing A. baumannii isolates obtained from Najaf hospitals. Isolates were identified according to API 20NE system and more confirmed using 16Sr RNA gene. Carbapenem susceptibility was assayed by microbroth dilution and other antibiotics usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Our findings are in contrast to the results reported by [22], who reported a sensitivity of 60% for the MHT. Similarly, [31,32]reported sensitivities of 33% and 20%, respectively, which are more consistent with our study's findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in contrast to the results reported by [22], who reported a sensitivity of 60% for the MHT. Similarly, [31,32]reported sensitivities of 33% and 20%, respectively, which are more consistent with our study's findings.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of carbapenemase-encoding genes, bla VIM was detected in 18% of the isolates, resembling the findings of [32] but differing significantly from the studies conducted by [33][34][35]. Interestingly, bla SPM was found in 50% of the isolates, contradicting the findings of [34], where none of the tested isolates carried this gene.…”
Section: Discussioncontrasting
confidence: 60%
“…2) . In the study in Iraq , Alsehlawi, andhiscolleagues who found 2(40%) A. baumannii isolates had blaOXA-23 genes positive in Najaf hospitals (18) . In contrast in Taiwan study , Lee, and hiscolleagues documented only one isolate (4%) of A. baumannii was harbored blaOXA-23 gene (25).…”
Section: Discussionmentioning
confidence: 94%
“…Out of the 10 A. baumannii isolates which were enrolled in this study, 6 (60%) isolates were found to produce the carbapenemase enzyme by MHT and all the remaining isolates were found to be carbapenemase negative . In a previous local study, Alsehlawi and hiscolleagues reported that 4 (33.3%) of A. baumannii isolates recovered from Najaf hospitals were confirmed as carbapenemase producer using modified Hodge's test, whereas the same isolate gave negative result with imipenem-EDTA synergy test (18). Another study from Croatia the Hodge test showed that 74% (72/97) of the A. baumannii isolates were positive for carbapenemase production (19) , whereas in a study from Pakistan has shown that 17 % of A. baumannii were positive for carbapenemase production by MHT (20).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation